Impact of Training Programs on Cooperative Management Efficiency - Kharel, Tika Ram; Dahal, Subhadra; Poudel, Shiva Raj (Brixton Scholarly Review, 2025)
The major objective of the study is to examine the impact of training frequency and the training quality on operational efficiency among the cooperatives in Nepal. Descriptive and casual comparative research designs have been used to identify the perceived relationship among the dependent and independent variables. All the data have been collected through the 5-points Likert scale structured questionnaires from the 360 respondents. The analysis tools used for the study are descriptive statistics, correlation analysis, and the multiple regression analysis. The results showed that both training frequency and the training quality have the significant positive impact on operational efficiency among the cooperatives operated in Nepal.